1997
DOI: 10.1111/j.1751-1097.1997.tb07956.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Global Erythemally Effective Irradiance by Clouds

Abstract: The role clouds play in the modification of global radiation is still a major uncertainty in the risk assessment of UV effects on ecological systems and human health. This study presents cloud transmission data obtained from measurements with Robertson-Berger meters and simultaneous cloud observations. The global transmission of erythemally weighted irradiance depends strongly on cloud amount and can be described by a cubic function. The comparison with results derived from long-term records of total global ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 25 publications
1
43
1
Order By: Relevance
“…This usually lasted for duration of less than an hour, most frequently of 10-20 min. Clouds generally reduce the incoming solar radiation flux to the Earth's surface as the solar disk is obscured, but they may also enhance solar irradiance, especially UV, when the solar disk is partly covered by clouds (Thiel et al, 1997;Degünther and Meerkötter, 2000). Values of 5-15% are commonly cited in the literature (Monteith and Unsworth, 1988;Robinson, 1977).…”
Section: Annual Variability Of Uv and Global Solar Irradiancementioning
confidence: 99%
“…This usually lasted for duration of less than an hour, most frequently of 10-20 min. Clouds generally reduce the incoming solar radiation flux to the Earth's surface as the solar disk is obscured, but they may also enhance solar irradiance, especially UV, when the solar disk is partly covered by clouds (Thiel et al, 1997;Degünther and Meerkötter, 2000). Values of 5-15% are commonly cited in the literature (Monteith and Unsworth, 1988;Robinson, 1977).…”
Section: Annual Variability Of Uv and Global Solar Irradiancementioning
confidence: 99%
“…Previous research, based on manual observations, has established that for cloud fractions less than 0.5 (4 okta), the attenuation of UV by cloud is independent of the cloud type, whereas for cloud fractions of 0.87 or greater (7 and 8 okta), there is a large difference in the attenuation of UV by high level clouds and by cumulus clouds (Thiel et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported on models to predict the global erythemal UV based on the cloud amount and cloud type (for example, Thiel et al 1997). Models have been developed for evaluating the global UVB based on a range of cloud parameters (Sabburg and Wong 2000b) and the diffuse solar UVA and UVB for partly cloudy skies (Grant and Gao 2003).…”
Section: Introductionmentioning
confidence: 99%